Storytelling for Systems Change: Listening to Understand - and Snow, Thea; Bandaranayaka, Asitha; Fyfe, Rachel; Wolf, Lila (Centre for Public Impact)
The second phase of our Storytelling for Systems Change work, has revealed new insights, raised questions, and offered a range of possibilities.